Consistent skin α-synuclein positivity in REM sleep behavior disorder – A two center two-to-four-year follow-up study. (May 2021) - Doppler, K.; Antelmi, E.; Kuzkina, A.; Donadio, V.; Incensi, A.; Plazzi, G.; Pizza, F.; Marelli, S.; Ferini-Strambi, L.; Tinazzi, M.; Mayer, G.; Sittig, E.; et al.
Abstract: Objective/methods: Phosphorylated alpha-synuclein (p-syn) in dermal nerves of patients with isolated REM sleep behavior disorder (iRBD) is detectable by immunofluorescence-labeling. Skin-biopsy-p-syn-positivity was recently postulated to be a prodromal marker of Parkinson's disease (PD) or related synucleinopathies. Here, we provide two-to four-year clinical and skin biopsy follow-up data of 33 iRBD patients, whose skin biopsy findings at baseline were reported in 2017. Results: Follow-up biopsies were available from 25 patients (18 positive at baseline) and showed consistent findings over time in 24 patients. One patient converted from skin-biopsy-negativity to -positivity. P-syn-positivity was observed in iRBD patients who still had a normal FP-CIT-SPECT two years later. Clinically, five of the 23 at baseline skin-biopsy-positive patients (21.7%) had converted to PD or dementia with Lewy bodies at follow-up, but none of the skin-biopsy-negative patients. Conclusions: Dermal p-syn in iRBD is most probably an early consistent marker of synucleinopathy and may support other indicators of conversion to manifest disease state. Highlights: Dermal p-syn deposition is consistent over time in patients with RBD. Only RBD patients with dermal p-syn deposition converted to manifest PD/DLB. Dermal p-syn-positivity was observed in patients who still had a normal FP-CIT-SPECT at follow-up.